Jaśkowski’s Discovery and Various Ways to Master Contradictions - Fazio, Davide; Jarmużek, Tomasz; Malinowski, Jacek; Mruczek-Nasieniewska, Krystyna (Logic and Logical Philosophy, 2025)
This paper presents the history of the world’s first school of paraconsistency: the Torunian School of Paraconsistent Logic. Its founding father is the Polish logician Stanisław Jaśkowski, who first formulated a system of paraconsistent logic. Both the approach he presented and the work of subsequent generations of logicians allow us to speak of the entire school. In this article, we present the characteristics of this school, comparing them with those of other national, but later, schools of paraconsistency. In addition to extensive factual information concerning Jaskowski’s discovery and subsequent development of this topic, we also refer to and comment on the latest works presented in this volume.